Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1186/1423-0127-18-84
|View full text |Cite
|
Sign up to set email alerts
|

Hesperetin-7,3'-O-dimethylether selectively inhibits phosphodiesterase 4 and effectively suppresses ovalbumin-induced airway hyperresponsiveness with a high therapeutic ratio

Abstract: BackgroundHesperetin was reported to selectively inhibit phosphodiesterase 4 (PDE4). While hesperetin-7,3'-O-dimethylether (HDME) is a synthetic liposoluble hesperetin. Therefore, we were interested in investigating its selectivity on PDE4 and binding ability on high-affinity rolipram-binding sites (HARBs) in vitro, and its effects on ovalbumin-induced airway hyperresponsiveness in vivo, and clarifying its potential for treating asthma and chronic obstructive pulmonary disease (COPD).MethodsPDE1~5 activities w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…Preliminary studies demonstrated almost always an increase in the numbers of neutrophils, eosinophils, macrophages and lymphocytes in the respiratory system of animals sensitized via OVA (Nabe et al, 2005;Nabe et al, 2011;Yang et al, 2011;Brandenberger et al, 2013;Kim et al, 2013). In this study, there was no difference between the two groups for eosinophilia and macrophage, with a slight difference in the number of lymphocytes (p=0.085).…”
Section: Discussionmentioning
confidence: 61%
“…Preliminary studies demonstrated almost always an increase in the numbers of neutrophils, eosinophils, macrophages and lymphocytes in the respiratory system of animals sensitized via OVA (Nabe et al, 2005;Nabe et al, 2011;Yang et al, 2011;Brandenberger et al, 2013;Kim et al, 2013). In this study, there was no difference between the two groups for eosinophilia and macrophage, with a slight difference in the number of lymphocytes (p=0.085).…”
Section: Discussionmentioning
confidence: 61%
“…or 3–30 µmol/kg o.p.) reduced all types of inflammatory cells and cytokines, including IL‐5 and tumor necrosis factor‐α (TNF‐α) levels in BAL fluid of methacholine‐sensitized mice (Yang et al ., ; Shih et al ., ). Our study revealed that hesperetin–naringenin, orange, and grapefruit juices each could significantly reduce infiltration of inflammatory cells to airway and mucus plug formation.…”
Section: Discussionmentioning
confidence: 98%
“…In accordance with the previous method and schedule, 13 the AHR of female BABL/c mice was assessed by measuring changes in the airway resistance (R L, cmH 2 O/mL/sec) and lung dynamic compliance (C dyn , mL/cmH 2 O) after challenge with aerosolized methacholine (MCh, 0.78~25 mg/mL) using the FlexiVent system (SCIREQ, Montreal, Quebec, Canada). Anesthetized (urethane 600 mg/kg and chloralose 120 mg/kg, i.p.…”
Section: Ahr In Vivomentioning
confidence: 99%